2014
DOI: 10.3171/2014.7.spine13846
|View full text |Cite
|
Sign up to set email alerts
|

Use of anteroposterior view fluoroscopy for targeting percutaneous pedicle screws in cases of spinal deformity with axial rotation

Abstract: Object Over the past decade percutaneous pedicle screws have become popular for the minimally invasive treatment of spinal disorders. However, until the last 5 years the presence of a significant spinal deformity was regarded as a relative contraindication for percutaneous instrumentation. Recent advances in surgical technique and intraoperative technology have made percutaneous fixation in complex spinal pathologies more commonplace. The authors report their experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
(13 reference statements)
0
21
1
1
Order By: Relevance
“…Careful patient selection is required for this minimally invasive operation, given that percutaneous pedicle screw fixation is heavily dependent on imaging for level confirmation, for example fluoroscopic guidance [22]. Patients with rotational deformities, or even obesity and osteopenia, may have anatomy which could obscure imaging guidance, and thus may not be suitable for percutaneous pedicle screw fixation [1]. Studies have also suggested other contradictions including multi-level vertebral fractures, pedicle fractures, adjacent body fractures, and severe neural deficits which require canal decompression [23].…”
Section: Discussionmentioning
confidence: 99%
“…Careful patient selection is required for this minimally invasive operation, given that percutaneous pedicle screw fixation is heavily dependent on imaging for level confirmation, for example fluoroscopic guidance [22]. Patients with rotational deformities, or even obesity and osteopenia, may have anatomy which could obscure imaging guidance, and thus may not be suitable for percutaneous pedicle screw fixation [1]. Studies have also suggested other contradictions including multi-level vertebral fractures, pedicle fractures, adjacent body fractures, and severe neural deficits which require canal decompression [23].…”
Section: Discussionmentioning
confidence: 99%
“…For rigid lumbosacral fixation in cMISS, Wang et al [ 39 ] reported feasibility and safety of percutaneous iliac screws placement without extensive muscle exposure. Fluoroscopic guidance is essential and recent advances for image-guided surgery with navigation or robotic guidance enhance safety and accuracy of the surgery [ 40 , 41 ].…”
Section: Percutaneous Pedicle Screw and Rod Placementmentioning
confidence: 99%
“…Whereas the dual fluoroscopy technique contributed to the high accuracy of screw placement on the axial plane and the optimal location of the screw top within the vertebra on lateral imaging, 12 it had a disadvantage of requiring more radiation exposure. 22 Without an expensive imaging support system, the technique of PPS insertion using dual fluoroscopy units is fairly accurate. However, the higher radiation exposure when using this technique compared with a navigation system is one important limitation.…”
Section: Discussionmentioning
confidence: 99%